DEVELOPING A BUSINESS MODEL CANVAS FOR ECO-TOURISM : INTEGRATING DESIGN THINKING AND DIGITAL MARKETING FOR SUSTAINABILITY - Febri Sari Siahaan; Susilowati Susilowati; Indra Bakti; Siti Muslyhah; Dwi Maylani Pertiwi (LPPM STIE Muhammadiah Bandung, 2026)
Ecotourism destinations in Indonesia continue to face challenges in aligning environmental stewardship, community participation, and sustainable business practices, particularly in rural sites such as Tebing Koja. This study aims to develop an integrated and sustainability-oriented business model by combining stakeholder insights, visitor perceptions, and strategic innovation through the Business Model Canvas (BMC), Design Thinking, and digital marketing approaches. The findings reveal that visitors highly depend on digital information clarity, social media visibility, and online ticketing convenience, highlighting the essential role of digital marketing in shaping destination trust and attractiveness. Stakeholder insights simultaneously emphasize needs related to safety, facility quality, environmental education, and inclusive community involvement. Quantitative results from 100 visitors confirm the strong influence of Digital Marketing and Design Thinking on Business Model Innovation, with innovation serving as a key driver of ecotourism sustainability. Mediation analysis further shows that innovative business practices significantly strengthen the impact of digital engagement and visitor-centered insights on sustainable outcomes. The integrated findings support the development of a comprehensive BMC tailored for Tebing Koja, outlining clear value propositions, customer segments, operational priorities, and partnership strategies. Overall, this study demonstrates that sustainability in rural ecotourism emerges not only from ecological preservation but also from digital readiness, human-centered design, and collaborative business innovation, offering a practical roadmap for strengthening destination competitiveness and long-term socio-environmental value